Building information modeling (BIM) implementations in the Turkish construction industry - Karahan, Uğur. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
The construction industry has always been highly signi cant for the national economy. Due to increasing pressures from clients to improve quality, reduce costs and speed up construction processes, Building Information Modeling (BIM) can be a key source of competitive advantage for construction companies. This study is investigates the critical success factors (CSFs) of successful BIM implementation. A questionnaire survey is designed and administered to both public and private sector participants. The questionnaire consists of three parts; the rst two parts deal with the general information and CSFs and third part with project speci c questions. Eighty-one respondents provided valid responses out of 244 questionnaire forms sent out. Based on the collected data, the relative importance of 16 potential CSFs for BIM projects in Turkey is examined. The results show that the three most important factors are: \availability of quali ed sta ", \e ective leadership", \availability of information and technology". Factor analysis indicated that proper factor groupings for the 16 CSFs are: human related factors, industry related factors, project related factors, policy related factors and resource related factors. Another objective of this research is to examine the application process of BIM in the construction sector with the parameters set out to shed light on the success of future projects. In order to achieve this, an extensive literature survey was conducted to nd the most appropriate components including the drivers, enablers, barriers, inputs, bene ts, and impacts. A total of 11 cases were investigated and ndings have been reported. Proposal of such a framework has considerable contributions to increasing BIM awareness of companies in Turkish construction industry and thereby assisting their on long-term strategies.
Keywords: Building information modeling.